Highly specific, membrane-permeant peptide blockers of cGMP-dependent protein kinase Iα inhibit NO-induced cerebral dilation - Dostmann, Wolfgang R. G. (The National Academy of Sciences, 2000)
Arrays of octameric peptide libraries on cellulose paper were screened by using (32)P-autophosphorylated cGMP-dependent protein kinase Iα (cGPK) to identify peptide sequences with high binding affinity for cGPK. Iterative deconvolution of every amino acid position in the peptides identified the sequence LRK(5)H (W45) as having the highest binding affinity. Binding of W45 to cGPK resulted in selective inhibition of the kinase with K(i) values of 0.8 μM and 560 μM for cGPK and cAMP-dependent protein kinase (cAPK), respectively. Fusion of W45 to membrane translocation signals from HIV-1 tat protein (YGRKKRRQRRRPP-LRK(5)H, DT-2) or Drosophila Antennapedia homeo-domain (RQIKIWFQNRRMKWKK-LRK(5)H, DT-3) proved to be an efficient method for intracellular delivery of these highly charged peptides. Rapid translocation of the peptides into intact cerebral arteries was demonstrated by using fluorescein-labeled DT-2 and DT-3. The inhibitory potency of the fusion peptides was even greater than that for W45, with K(i) values of 12.5 nM and 25 nM for DT-2 and DT-3, respectively. Both peptides were still poor inhibitors of cAPK. Selective inhibition of cGPK by DT-2 or DT-3 in the presence of cAPK was demonstrated in vitro. In pressurized cerebral arteries, DT-2 and DT-3 substantially decreased NO-induced dilation. This study provides functional characterization of a class of selective cGPK inhibitor peptides in vascular smooth muscle and reveals a central role for cGPK in the modulation of vascular contractility.